2017
DOI: 10.18805/ijar.b-3293
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary supplementation of vitamin E, zinc, and chromium supplementation on growth performance and hematological characteristics of broiler chickens

Abstract: The study investigated the effect of supplementation of Vitamin E, Zn and Cr on growth performance and hematological characteristics of broiler chickens. The 240 day old Cobb 400 chicks were randomly distributed in eight groups consisting of 30 chicks in each. These chicks were kept on deep litter houses comprising of wood shavings. The supplementation of Vitamin E, zinc and chromium either individually or in combination improved the feed conversion ratio and body weight gain in broiler chicks. The body weight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…Chromium is a trace element involved in carbohydrates, lipids, protein and nucleic acid metabolism and its growth-promoting effect was reported previously (Ali et al 2018). Improved productive parameters in stress conditions under chromium or combinations of chromium with other antioxidants were published in terms of weight gain or feed efficiency (Perai et al 2014;Ali et al 2018).…”
Section: Discussionmentioning
confidence: 94%
“…Chromium is a trace element involved in carbohydrates, lipids, protein and nucleic acid metabolism and its growth-promoting effect was reported previously (Ali et al 2018). Improved productive parameters in stress conditions under chromium or combinations of chromium with other antioxidants were published in terms of weight gain or feed efficiency (Perai et al 2014;Ali et al 2018).…”
Section: Discussionmentioning
confidence: 94%
“…These findings are agreement with Tawfeek et al (2014) who reported that supplementation with 250 mg Vit.C + 250 mg Vit.E or 0.5 mg Cr to stressed broilers (36 °C, RH 75%) significantly increased BW and BWG, decreased FCR and M % but did not change FI. In contrast, Ali et al (2018) reported that adding Vit.E, Zn, Cr individually or in a combination to broiler diets increased FI. The positive effect of combination Vit.+Min.…”
Section: Growth Performance and Mortalitymentioning
confidence: 96%
“…To overcome HS effects in broiler chicks through nutritional management strategies: two ways have been used 1) feed restriction (FR) methods (Abdel-Hafeez et al 2017); 2) dietary supplementation of feed additives (antioxidants, minerals, vitamins, amino acids, probiotics, prebiotics, etc. ) (Ali et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The combination of vitamin C and vitamin E in broiler diets markedly increased BWG and decreased FCR (Attia et al, 2017). Ali et al (2018) showed that dietary supplementation with vitamin E, Cr, and Zn either individually or in combination enhanced BWG and FCR in broilers. The harmful effects of HS in broiler chicks are a result of a decrease in FI, increase in body temperature, depressed immune response, declined energy bioavailability in cells, digestibility of nutrients, metabolism, and absorption, damage in endocrine functions, disorders in the role and structure of intestinal epithelium, and variations in microbiota of the gut (Lara and Rostagno., 2013;Wang et al, 2018).…”
Section: Growth Performance and Mortalitymentioning
confidence: 99%